2019
DOI: 10.1002/qua.25849
|View full text |Cite
|
Sign up to set email alerts
|

Dieter Cremer's contribution to the field of theoretical chemistry

Abstract: This legacy article reviews the contributions of Dieter Cremer (1944‐2017) to the field of theoretical chemistry, highlighting his major accomplishments in method development and applied quantum chemistry, which has led to many advances in the field. His work reflects an extraordinary breadth and deep understanding of theory, which is needed to solve complex chemical problems. His passion for science has inspired many colleagues in the past and will do so in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 322 publications
(342 reference statements)
0
20
0
Order By: Relevance
“…Recent developments by Konkoli and Cremer ( Konkoli and Cremer, 1998a ; Konkoli and Cremer, 1998b ; Kraka et al, 2020 ) have allowed for the mass decoupling of the normal modes of vibration, to recast the eigenvectors onto a new set of modes, termed the local modes of vibration, that correlate directly with individual bond stretches, angle bends etc. Their work has shown that the resulting local-mode force constants thus obtained are a direct measure of bond strength ( Kraka and Cremer, 2019 ). Thus performing local mode analysis across a broad range of molecules (both energetic and non-energetic) provides information on the relationship between bond length and bond strength of the most common chemical bonds in EMs, which has the potential to be utilised for molecular design.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments by Konkoli and Cremer ( Konkoli and Cremer, 1998a ; Konkoli and Cremer, 1998b ; Kraka et al, 2020 ) have allowed for the mass decoupling of the normal modes of vibration, to recast the eigenvectors onto a new set of modes, termed the local modes of vibration, that correlate directly with individual bond stretches, angle bends etc. Their work has shown that the resulting local-mode force constants thus obtained are a direct measure of bond strength ( Kraka and Cremer, 2019 ). Thus performing local mode analysis across a broad range of molecules (both energetic and non-energetic) provides information on the relationship between bond length and bond strength of the most common chemical bonds in EMs, which has the potential to be utilised for molecular design.…”
Section: Introductionmentioning
confidence: 99%
“…3c-4e HVI bonding (3c-4e HVIB) draws comparisons to the secondary bonding interaction due to the weak bond strength, high reactivity, and long internuclear distances exceeding covalent bond lengths [37]. 3c-4e HVIB also shares similarities with non-covalent interactions, along with hydrogen bonding [38][39][40], XB [35,[41][42][43], pnicogen bonding [43][44][45], chalcogen bonding [43,46], and tetrel bonding [47]. XB is a non-covalent interaction between an electrophilic halogen (X) and a nucleophile with a lone pair (lp(A)) of donating electrons [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…The well depth, which is the difference in energy between the local minimum and TS, can be regarded as the energy indicator for the kinetic stability of interanion interaction and a measurement of its strength as well. Alternatively, the local bond stretching force constant ( k ), which basically stands for the curvature of an energy profile along the direction of a specified chemical bond, can be considered as an “in situ” indicator for the intrinsic bond strength. As k has provided novel insights into conventional and unusual chemical bonds, it could serve as an indicator for interanion interactions in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Profiles of electrostatic interactions and total interaction energies were further analyzed using the AMOEBA polarizable force field with QM-based atomic multipoles, ,, aiming at a concise interpretation for these interanion phenomena. Based on our findings, a few novel complexes with attractive interanion contacts were constructed (9, 11, 13, and 15 in Scheme ) with a group of simplified molecular capsules. In addition, the local bond stretching force constant ( k ) as a new indicator for interanion H/XB was also inspected.…”
Section: Introductionmentioning
confidence: 99%